2009
DOI: 10.1080/00927870802186227
|View full text |Cite
|
Sign up to set email alerts
|

Some Remarks on Borel Type Ideals

Abstract: We give new equivalent characterizations for ideals of Borel type. Also, we prove that the regularity of a product of ideals of Borel type is bounded by the sum of the regularities of those ideals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 7 publications
1
13
0
Order By: Relevance
“…In [6], Chardin, Minh and Trung proved that if I and J are monomial complete intersections, then reg(IJ) ≤ reg(I) + reg(J). Cimpoeaş proved that for two monomial ideals of Borel type I, J, reg(IJ) ≤ reg(I) + reg(J), [7]. Caviglia in [5] and Eisenbud, Huneke and Ulrich in [9] studied the more general problem of regularity of tensor products and various Tor modules of R/I and R/J.…”
Section: Introductionmentioning
confidence: 99%
“…In [6], Chardin, Minh and Trung proved that if I and J are monomial complete intersections, then reg(IJ) ≤ reg(I) + reg(J). Cimpoeaş proved that for two monomial ideals of Borel type I, J, reg(IJ) ≤ reg(I) + reg(J), [7]. Caviglia in [5] and Eisenbud, Huneke and Ulrich in [9] studied the more general problem of regularity of tensor products and various Tor modules of R/I and R/J.…”
Section: Introductionmentioning
confidence: 99%
“…, x j ) ∞ ), (∀)1 ≤ j ≤ n. The Mumford-Castelnuovo regularity of I is the number reg(I) = max{j − i : β ij (I) = 0}, where β ij 's are the graded Betti numbers. The regularity of the ideals of Borel type was extensively studied, see for instance [12], [1] and [5]. In the first section, we study the invariant sdepth(I), for an ideal of Borel type.…”
Section: Introductionmentioning
confidence: 99%
“…Proposition 5.2] or[5, Corollary 1.2], it follows that I is an ideal of Borel type. As a direct consequence of Lemma 1.3 and Proposition 1.4, we get the following corollary.…”
mentioning
confidence: 99%
“…In [4,Proposition 1], Mircea Cimpoeas observed that the afore mentioned property is preserved under several operations, such as sum, intersection, product, colon. For a monomial ideal I of Borel type, note that I : m ∞ = I : m r holds for r >> 0, thus the saturation I : m ∞ is a monomial ideal of Borel type.…”
Section: Introductionmentioning
confidence: 99%